THE EVIDENCE FOR LATE-ONSET PRE-ECLAMPSIA AS A MATERNOGENIC DISEASE OF PREGNANCY. (19th March 2013) - FERRAZZI, ENRICO; STAMPALIJA, TAMARA; AUPONT, JEAN EDGARD
Abstract : It is our opinion that the evidence from epidemiological observations, clinical trials and biological studies is strong enough to support the view of different origin and phenotypes of pre-eclampsia: placental, which usually occurs (but not exclusively) early in pregnancy and is associated with poor early placentation of different severity with subsequent restriction of foetal growth, at different stages of gestation; and maternogenic, which generally occurs late in pregnancy and it is not related to placental insufficiency and foetal growth restriction.